Development of Model System for Cost-Effective Pico-Hydro Turbine - MUSA@OTHMAN, MASJURI (IEEE Explore, 2011)
One of the main obstacles of rural electrification programme is to find an alternative energy to replace power generated by generator. The ever increasing fuel price and its cost of transportation to the remote location limited the availability of electricity to certain time of the day. Since the rural settlement usually located near water source, renewable energy based on hydro is suggested. This paper will discuss about the development of model system for cost-effective pico-hydro turbine. The size of the turbine will be based on low flow and low head application. Two types of turbine, propeller or also known as axial-flow and cross-flow, are evaluated under these conditions. Both of the turbines were installed in one model system equipped with storage tanks and piping system. Centrifugal pump is used to ensure the circulation of the water between main storage tank into the flowing tank simulating the run-of river application for pico hydro system. The head of the model system is fixed with variable parameter of water flow rate is controlled by using controller valve and flow meter for power data collection for each turbine. The performance of both turbines were also simulated and evaluated by using CFD’s software. Techno-economics evaluations are done so that the model of the system will be able to select the optimum size of the turbine based on the flow rate for a cheap efficient and costeffective hydro turbine.